Eptinezumab for the preventive treatment of episodic and chronic migraine: a narrative review - Irimia, Pablo; Santos-Lasaosa, Sonia; Pozo-Rosich, Patricia; Leira, Rogelio; Pascual, Julio; Láinez, José Miguel (Frontiers in Neurology, 2024)
Eptinezumab, a monoclonal antibody that targets calcitonin gene-related peptide (CGRP), was recently approved in Europe for the prophylactic treatment of migraine in adults who have at least four migraine days a month. Eptinezumab is administered by intravenous infusion every 12 weeks., which is a longer interval between doses than other CGRP-targeting treatments. During recent months, a considerable amount of evidence from eptinezumab trials has been published. The aim of this review is to describe the existing evidence on the tolerability, safety and efficacy of eptinezumab in patients with migraine. Data from randomized (PROMISE-1, PROMISE-2, RELIEF and DELIVER) and open-label (PREVAIL) phase 3 clinical trials have demonstrated the favourable effect of eptinezumab in migraine symptoms from first day of treatment. These studies showed that eptinezumab results in an overall reduction in mean monthly migraine days (MMDs), increases in the ≥50% and ≥75% migraine responder rates (MRRs) and improvements in patient-reported outcome measures in both patients with episodic migraine (EM) and with chronic migraine (CM), including for patients who failed previous preventive treatments. The RELIEF trial also showed that eptinezumab, within 2 h of administration, reduced headache pain, migraine-associated symptoms and acute medication use when administered during a migraine attack. Eptinezumab benefits manifested as early as day 1 after dosing and with the subsequent doses lasted up to at least two years. Treatment-emergent adverse events reported by ≥2% of patients included upper respiratory tract infection and fatigue. Current evidence demonstrates that eptinezumab has a potent, fast-acting, sustained migraine preventive effect in patients with EM and CM. Eptinezumab has also shown to be well tolerated, supporting its use in the treatment of patients with migraine and inclusion in the current migraine therapeutic options.